Perlindungan Hukum Konsumen Terhadap Transaksi Online dan Pembuktian Akta Elektronik Sebagai Bukti dalam Sengketa Perdata di Era Digitalisasi - Prasetia, Ade Nufi; Kusworo, Anjar Dwi; Rosidi, M. (JATIJAJAR LAW REVIEW, 2026)
The digital era is revolutionising online transactions in Indonesia, valued at hundreds of trillions of rupiah, but it also poses risks of fraud, product discrepancies, and difficulties in proving civil disputes due to doubts about the integrity of electronic deeds. The purpose of this research is to analyse the legal consumer protection framework based on Law No. 8/1999 on Consumer Protection and Government Regulation No. 80/2019, as well as the evidentiary strength of electronic deeds in accordance with Law No. 11/2008 on Electronic Information and Transactions jo. No. 19/2016, in order to identify challenges and solutions for legal certainty. Using a normative legal approach with secondary analysis of regulations, journals, books, and court decisions through literature review. The results show that regulations recognise electronic deeds as valid evidence if their integrity is guaranteed via digital certification, but challenges in metadata verification and e-commerce oversight hinder effectiveness; strengthening SEMA MA, blockchain, and judicial education is needed.